Exploring the influence between WP behavior & knowledge in maintaining tax compliance - Novika Frialestari Harianja; Royana Ferinia (Institute of Computer Science (IOCS), 2023)
This research discusses factors that can infuence taxpayer behavior and knowedge on taxpayer compiance. One of these factors is taxpayer compiance. This research exp s that peope's behavior and knowedge regarding compiance with paying taxes is sti reativey ow. Therefore, there are chaenges in achieving higher eves of compiance. The instrument used was a questionnaire which was distributed directy. The method used by researchers is a quantitative method with primary data processed from 100 respondents in Parongpong District. The data anaysis technique used in this research is Structura Equation Model ing (SEM) and anaysis using SmartPLS. The resuts of this research show that behavior has a significant effect on taxpayer knowedge, behavior has an effect on taxpayer compiance, but taxpayer knowedge does not have a significant effect on taxpayer compiance and behavior aso does not have a significant effect on taxpayer compiance through taxpayer knowedge. The novelty of the study shows that taxpayer awareness eads to compiance, but the knowedge aone isn't aways enough to get peope to foow the rues.